Characterization of dSnoN and its relationship to Decapentaplegic signaling in Drosophila. - Barrio, R.; López-Varea, A.; Casado, M.; de Celis, J.F. (Developmental Biology, 2007)
Vertebrate members of the ski/snoN family of proto-oncogenes antagonize TGFbeta and BMP signaling in a variety of experimental situations. This activity of Ski/SnoN proteins is related to their ability to interact with Smads, the proteins acting as key mediators of the transcriptional response to the TGFbeta superfamily members. However, despite extensive efforts to identify the physiological roles of the Ski/SnoN proteins, it is not yet clear whether they participate in regulating Activin and/or BMP signaling during normal development. It is therefore crucial to examine their roles in vivo mostly because of the large number of known Ski/SnoN-interacting proteins and the association between the up-regulation of these genes and cancer progression. Here we characterize the Drosophila homolog to vertebrate ski and snoN genes. The Drosophila dSnoN protein retains the ability of its vertebrate counterparts to antagonize BMP signaling in vivo and in cultured cells. dSnoN does not interfere with Mad phosphorylation but it interacts genetically with Mad, Medea and dSmad2. Mutations in either the Smad2-3 or Smad4 putative binding sites of dSnoN prevent the antagonism of dSnoN towards Dpp signaling, although homozygous flies for these mutations or for a genetic deficiency of the locus are viable and have wings of normal size and pattern.